OCORRÊNCIA DE ENDOPARASITOS EM GATOS DE CUIABÁ, MATO GROSSO, BRASIL - Gavioli, Fernando Antonio; Borsa, Adriana; Diogo, Joaquim Elias; Pinto, Andressa Zelenski de Lara; Azevedo, Ludmila Silva; Sousa, Valéria Regia Franco (Archives of Veterinary Science, 2011)